National Prevalence and Effects of Multiple Chemical Sensitivities - Steinemann, Anne (J Occup Environ Med, 2018)
OBJECTIVE: The aim of this study was to assess the prevalence of multiple chemical sensitivities (MCS), its co-occurrence with asthma and fragrance sensitivity, and effects from exposure to fragranced consumer products. METHODS: A nationally representative cross-sectional population-based sample of adult Americans (n = 1137) was surveyed in June 2016. RESULTS: Among the population, 12.8% report medically diagnosed MCS and 25.9% report chemical sensitivity. Of those with MCS, 86.2% experience health problems, such as migraine headaches, when exposed to fragranced consumer products; 71.0% are asthmatic; 70.3% cannot access places that use fragranced products such as air fresheners; and 60.7% lost workdays or a job in the past year due to fragranced products in the workplace. CONCLUSION: Prevalence of diagnosed MCS has increased over 300%, and self-reported chemical sensitivity over 200%, in the past decade. Reducing exposure to fragranced products could help reduce adverse health and societal effects.